Give the values of a, b, and c from the general form of the equation (2x + 1)(x - 2) = 0.
a=2, b=-3, c= -2
a=2, b=5, C=-2
a=3, b=1, c= -1

Respuesta :

[tex](2x+1)(x-2) = 0[/tex]

Multiplying the factors we obtain:

[tex]2x\cdot x+2x\cdot (-2)+1\cdot x+1\cdot (-2)=0[/tex]

[tex]2x^2-4x+x-2=0[/tex]

[tex]2x^2-3x-2=0[/tex]

The general form of quadratic equation is:

[tex]ax^2+bx+c=0[/tex]

Therefore,

[tex]a=2[/tex]

[tex]b=-3[/tex]

[tex]c=-2[/tex]

The correct answer is the first one.

ACCESS MORE